El informe del perito Otto Niemeyer - Liliedal, Augusto M. (1961)
The creative plan and statute of the Central Bank of the Argentine Republic prepared by the Englishman Sir Otto Niemeyer, established immediate and mediate functions. Among the first mentioned and which justified its rapid creation were: to adjust the volume of credit and the consequent demand for money, assuming the functions of the Conversion Bank, re discount commission and exchange control; to exercise a supervision over the other deposit banks, conserving their last cash reserves and government credit balances, apart from the intervention in the foreign debt; and to act as correspondent or agent for the other central bank. Among the second is included the intervention in the definite stability of the peso, since it was not timely to endeavour to do so immediately due to the international conclusion existing at that time